Training on Installation, Configuration and Usage of WRF-Hydro model - Gezahegn, Addisu; Tefera, Gulilat; Demissie, Teferi Dejene; Mersha, Yonas; Bekele, Tamrat (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Understanding the mechanisms leading to heavy precipitation events and accurate modelling of the surface hydrology is crucial for producing a reliable flood early warning system. In this workshop we used uncoupled WRF-Hydro model, an open-source community model, for the flash flood prediction. The model can also be used for a range of projects, including regional hydro-climate impacts assessment, seasonal forecasting of water resources, and land-atmosphere coupling studies. The underlying goal of WRF-Hydro development is to improve prediction skill of hydro-meteorological forecasts using science based numerical prediction tools. In addition to the hydrological modelling, understanding the atmospheric process is equally important to get a better insight regarding flood events. Large scale atmospheric and surface fields associated with selected extreme precipitation events are analysed in this workshop using ERA5 reanalysis, to understand the processes leading to such heavy precipitation events.